Environmental Management, Climate Change, CSR, and Governance in Clusters of Small Firms in Developing Countries: Toward an Integrated Analytical Framework - Puppim de Oliveira, Jose A.; Jabbour, Charbel Jose Chiappetta [UNESP] (SAGE Publications, 2017)
One of the key debates in the literature on small and medium enterprises (SMEs) and corporate social responsibility (CSR) in developing countries has to do with the role that local industrial districts, or so-called industrial clusters, play in the promotion of CSR in those countries. While there is now an embryonic literature on this subject, we lack systematic, integrated analytical frameworks that can improve our understanding of the role that governance of clusters play in addressing CSR concerns in SMEs in developing countries. This article develops such a conceptual framework drawing on the literatures on cluster governance, CSR, SMEs, and environmental management (EM) as they relate to the developing countries. The authors argue that environmental improvements in SME clusters can be achieved through three basic types of cluster governance: legal enforcement, supply chain pressure, and voluntary engagement in CSR. The proposed framework is an attempt to show how each type of cluster governance is likely to induce different responses in cluster-based SMEs. These responses are related to stages of CSR in which SMEs engage, the barriers to EM they face, the types of EM practices they use, the climate change strategy types they use, and the kinds of benefits that accrue to SMEs from engagement in CSR. The authors put foward a framework that can be useful for both academics and practitioners as they seek to reflect on the interconnectedness of these themes from a research, policy, and practice perspective.
Keywords: climate change; clusters; corporate social responsibility; developing countries; environmental management; governance; small enterprises